A development of collaboration model for strategic engagement between SME Malaysia and universities using attitudinal parameter in the context of university industry collaboration - Kartina, Johan@Rahmat (2023)
The research is inspired by the fact that the collaboration between university and industry in Malaysia has been for so many years dominantly operated based on entrepreneurial university concept. This entrepreneurial university concept focus on academic research commercialisation outputs with companies which has R&D facilities and favour a formal mode of interaction under the innovation by research strategy. SMEs however being the major contributor of the national economic landscape favour collaboration based on informal mode has missed its significance in the existing national strategic collaborative platform due to the absence of its undefined interactions and strategic model for quantifying its UIC performance. The aim of the study is to assess and understand the university-industry interaction in the form of collaboration model termed as UniversityEnterprise-Collaboration (UEC) between university and SME. The assessment is conducted by integrating attitudinal parameter to the engagement characteristics of a classic university-industry collaboration (UIC) interaction design under the concept of Engaged Scholarship (ES). In this study a structured survey instrument is developed from selected engagement parameters based on literature to study the interaction parameters among the SME practitioners and university researchers. The targeted respondents must be at least once involved in collaborative research projects with minimum criteria of three years’ service in the university and five years of service in SME. The data is statistically analysed based on relative importance value followed by DOE method and regression analysis to obtain the instrumental UEC collaboration design which is developed into formulations of mathematical expressions that reflect the UEC interactive design with quantifiable means. The instrumental model is considered as a linear model because it does not carry the ‘trust’ element that dictates the core component of UEC relationship. Therefore, to elementally develop the instrumental model to become a competent one, a behavioural dimension which consists of the collaborative actors’ functional characteristics i.e., knowledge and behaviour is integrated in the later stage of the model development to produce a characterized model that reflects the attitudinal behaviour of the U-SME collaboration actors. This competent model which is characterized with the actors’ attitudes is now having the mathematical function which enable the UEC performance to be of a measurable value because it is embedded with the UEC contextual interaction designed to achieve innovativeness in SMEs. The development of the competent model for UEC is a significant attempt to realize a collaborative model because it enables the engagement strength of the collaborative interaction between university and SME (UEC) to be of a measured value (EV). The competence in the UEC model is regarded as strategic to SMEs due to these three elements: (i) integration of UEC actors’ intrinsic attitudinal element (a) knowledge and (b) behaviour to the mathematical equation (ii) the introduction of the Innovator Definition (ID) that reflects the actor’s role in innovation strategy and (iii) the embedding of Knowledge Creation Descriptors (KDC) for the UEC conceptual knowledge creation in achieving innovativeness. The measurable performance using the mathematical expressions in the UEC model is expected able to help the universities and SMEs to strategize their collaboration partners effectively even at the point of early collaboration phase and sustain the U-SME relationship in a tangible and effectively monitored collaboration which benefits both actors in the name of innovation.